FACILITATION OF LEFT DORSOLATERAL PREFRONTAL ACTIVITY BY tDCS AND NEUROFUNCTIONAL TRAINING IN CHILDREN WITH AUTISM SPECTRUM DISORDER: A RANDOMIZED, PLACEBO-CONTROLLED, DOUBLE-BLIND CLINICAL TRIAL (CIPEEX, 2025)
The aim of the study is to compare the effects of ten sessions of neurofunctional training associated with active anodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex versus sham on the Activity and Participation domain of the ICF in children with ASD.This is a randomized, placebo-controlled, double-blind clinical trial involving 24 children diagnosed with ASD, aged between three and eight years. The children will be randomly assigned to two groups: Experimental group - neurofunctional training associated with anodal tDCS on the left dorsolateral prefrontal cortex and Control group - neurofunctional training associated with placebo tDCS. Participants will be assessed one week before, and one week and one month after the end of the intervention, using the Childhood Autism Rating Scale, Functional Strength Assessment, the 10-m Walk Test, the Timed Up and Go, the Pediatric Balance Scale, and the Participation and Environment Measure – Children and Youth (PEM-CY). The interventions will consist of five sessions per week, carried out over two consecutive weeks. Neurofunctional training and tDCS application will be performed synchronously for 20 minutes of each session. Neurofunctional training will consist of an activities circuit (10 minutes) and treadmill gait training (10 minutes). tDCS will be applied to the left dorsolateral prefrontal cortex at an intensity of 1mA. The results will be analyzed statistically assuming a significance level of p≤0.05.
Keywords: autism spectrum disorder; gait, balance; child; physical therapy; transcranial direct current stimulation